Прогноз розвитку внутрішнього ринку туристичних послуг України - Захарченко, Олена Григорівна; Захарченко, Елена Григорьевна; Zakharchenko, Olena; Бакіна, Тетяна Володимирівна; Бакина, Татьяна Владимировна; Bakina, Tetiana; Почерніна, Наталя Вікторівна; Почернина, Наталья Викторовна; Pochernina, Natalia (My University, 2021)
UK: В статті проаналізовані основні показники розвитку туризму в Україні, зокрема обсяги капіталовкладень, динаміку доходу від надання туристичних послуг, загальний вклад туризму в ВВП. Проведено структурний аналіз динаміки туристичних потоків України за 2013-2019 роки. Виявлена суттєва перевага виїзного туризму порівняно з внутрішнім туризмом. Побудовано регресійну модель, яка відображає залежність між кількістю внутрішніх туристів та такими факторними ознаками як: транспортний пасажирообіг, середній рівень заробітної плати та кількість туристичних агенцій. EN: In a pandemic, the economy must adapt to new conditions in order to minimize the risks that arise. One of the areas of the economy that is most affected by the pandemic is travel and tourism (T&T). If at the beginning of the XXI century tourism showed high indicators of development, then in 2020 the T&T sphere approached the limit of sur-vival, according to many experts' estimates. An effective way to preserve the country's tourism potential under these conditions is to develop domestic tourism. This research aims to analyze the development indicators of the tourism sector in Ukraine and assess the prospects for the development of the domestic tourist services market based on a correlation and regression model. An analysis of the main indicators of tourism development in Ukraine is presents the article. In particular, these are such indicators as the volume of capital investments, the dynamics of income from the provision of tourist services, and the total contribution of tourism to GDP. A structural analysis of the dynamics of tourist flows in Ukraine for 2013-2019 was carried out. A significant advantage of outbound tourism in comparison with domestic tourism was revealed. A regression model was constructed. This model reflects the relationship between the number of domestic tourists and such factor characteristics as: transport passenger turnover, average salary level and the number of travel agencies. The inverse relationship between the dynamics of the number of domestic tourists and the number of travel agencies was revealed. It was concluded that it would be advisable for the state to encourage small forms of management in the tourism industry, which are focused on creating tourist products of local significance. A direct relationship between the average salary, passenger traffic and the number of domestic tourists was proved. The calculated forecast indicates the possibility of increasing the number of domestic tourists in Ukraine in 2020 by 6%, in 2021 by 6%, in 2022 by 5%. Priority means and instruments of state regulation in the field of Ukrainian T&T were defined in order to stimulate the development of small forms of management. Among such means and instruments: the creation of specialized institutions capable of coordinating tourism activities in the direction of implementing Sustainable Development Goals; public-private partnership; inter-municipal cooperation; the creation of tourism clusters; the latest financial means, including crowdfunding; information support and IT infrastructure and others. Attention was focused on the need to develop such promising types of Tourism for small businesses as: event, sports and recreation, environmental, gastronomic, wine, agricultural tourism, etc.
Forecast of development of tourist services in the ukrainian domestic market
Keywords: ринок туристичних послуг; внутрішній туризм; пасажирообіг; кореляційно-регресійна модель; прогноз; tourism services market; domestic tourism; passenger turnover; correlation and regression model; forecast